CREATIVITY AND JOURNALISTIC SKILLS IN TV SHOWS (TAMADDUN NURI JURNALI, 2024)
The article discusses the impact of cultural and educational programs on children's education in the mass media and the fact that some problems arise in the spirituality of young people, and the negative impact of such programs on our national spirituality, especially on the education of the young generation. spoken. Accordingly, the article analyzes and expresses opinions on the shows that are taking place on television today.